2007
DOI: 10.1159/000109266
|View full text |Cite
|
Sign up to set email alerts
|

Detrended Fluctuation Analysis of Heart Rate Variability in Normal and Growth-Restricted Fetuses

Abstract: Background: Detrended fluctuation analysis (DFA) has recently been validated as an excellent method by which to analyze heart rate variability and distinguish healthy subjects from patients with various types of the cardiac nervous system dysfunction. Methods: One hundred and nineteen fetal heart rate (FHR) recordings obtained from healthy normal fetuses and 68 recordings obtained from small-for-gestational-age (SGA) fetuses were analyzed by DFA to examine gestational and pathologic changes of the scaling expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…• In IUGR fetuses reduced HRV indices were shown that correspond to lAMP using CTG recordings (Nijhuis et al 2000). Decreased HRV complexity in IUGR fetuses has been described in CTG recordings (lyapunov exponent (LE) (Kikuchi et al 2008), Lempel Ziv complexity (LZC) and multiscale entropy (MSE) of approximate entropy (ApEn) and sample entropy (SampEn) (Ferrario et al 2009)) across the age range from 27 to 34 WGA. It should be noted that these indices of complexity, obtained from the CTG based heart rate signal, correspond to long-term behavior.…”
Section: Discussionmentioning
confidence: 90%
“…• In IUGR fetuses reduced HRV indices were shown that correspond to lAMP using CTG recordings (Nijhuis et al 2000). Decreased HRV complexity in IUGR fetuses has been described in CTG recordings (lyapunov exponent (LE) (Kikuchi et al 2008), Lempel Ziv complexity (LZC) and multiscale entropy (MSE) of approximate entropy (ApEn) and sample entropy (SampEn) (Ferrario et al 2009)) across the age range from 27 to 34 WGA. It should be noted that these indices of complexity, obtained from the CTG based heart rate signal, correspond to long-term behavior.…”
Section: Discussionmentioning
confidence: 90%
“…In a later study Schneider et al, reported a difference in SDNN and RMSSD where one-third of the IUGR study population included compromised fetuses with only segments from the quiet sleep state analyzed [17]. Further, Detrended Fluctuation Analysis (DFA) of fetal heart-rate tracings has shown that, even though the normal fetuses’ short-term (α 1 ) scaling exponent is not significantly different from that of IUGR fetuses or those deemed small for gestational age (SGA), the long-term (α 2 ) scaling exponent of IUGR/SGA were significantly higher than that of normal fetus, indicating that heart-rate dynamics of IUGR fetuses are different from those of normal healthy fetus [25]. This implies that DFA shows the difference between low-risk and IUGR/SGA fetuses only in low-frequency components but not in high-frequency components.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum Lyapunov exponent (MLE) as an estimate of predictability of a dynamic system, was reported to be significantly lower for IUGR cases than control (Kikuchi et al , 2006). The authors also showed Detrend Fluctuation Analysis (DFA) can be used to separate IUGR cases from normal controls (Kikuchi et al , 2008). It was further supported by Ferrario et al, who found significantly higher DFA values of long-term scaling exponents for IUGR cases (Ferrario et al , 2009b).…”
Section: Application Of 1d-dus In Pathological Conditionsmentioning
confidence: 99%